Building the knowledge base for non-combinable codes according to the Korean Standard Classification of Diseases - Kim, Mijung; ., . (International Journal of Engineering and Technology, 2018)
The purpose of this study is to develop a knowledge base for non-combinable combinatorial codes to improve the accuracy of disease classification. We defined the rules related to non-combinable codes according to the list of code pairs proposed by the HIRA and the KCD-7 classification rules. A knowledge base was created according to defined rules and verified. To validate the knowledge base, inpatients who were billed for diabetes mellitus in December 2016 were selected as the subject of the study. As a result, the number of combinatorial codes proposed by the HIRA was 1,195, but the number of code pairs generated in the knowledge base was 25,439. Non-combinable codes by confirming with an indication of the HIRA have discovered 1,391 cases. As a result of verification with the code pair of the proposed knowledge base, 100 combinations were found. Non-combinable codes by confirming with an indication of the HIRA have discovered 1,391 cases. As a result of verification with the code pair of the proposed knowledge base, 3,525 combinations were found. It is meaningful that a convenient authoring tool that can automatically catch combinatorial codes was developed to build a knowledge base.Â Â